The family of ideal values for cooperative games - Wenna Wang; Hao Sun; Rene van den Brink; Genjiu Xu (Tinbergen Institute, 2018)
In view of the nature of pursuing profit, a selfish coefficient function is employed to describe the degrees of selfishness of players in different coalitions, which is the desired rate of return to the worth of coalitions. This function brings in the concept of individual expected reward to every player. Built on different selfish coefficient functions, the family of ideal values can be obtained by minimizing deviations from the individual expected rewards. Then we show the relationships between the family of ideal values and two other classical families of values: the procedural values and the least square values. For any selfish coefficient function m, the m-ideal value is characterized by efficiency, linearity, m-equal-expectation player property and nullifying player m-punishment property. We also provide an interpretation of a dynamic process for the m-ideal value. As two dual cases in the family of ideal values, the center-of-gravity of imputation-set value (CIS value) and the equal allocation of nonseparable costs value (EANS value) are raised from new axiomatic angles.
Keywords: C71; 330; Game theory; m-Individual expected reward; The family of ideal values; Dynamic process; CIS and EANS values